2023
DOI: 10.12688/routledgeopenres.17926.1
|View full text |Cite
|
Sign up to set email alerts
|

What is wrong with conspiracy beliefs?

Sinan Alper,
Onurcan Yilmaz

Abstract: The majority of psychological research highlights the role of lapses in rational thinking as a significant contributing factor to conspiracy beliefs (CBs). However, historical examples demonstrate that not all CBs are inherently incorrect. In this paper, we propose a more nuanced approach, suggesting that instead of universally labelling CBs as false or adopting an agnostic stance towards their veracity, it is beneficial to assess the plausibility of each CB individually along a continuum. To achieve this, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…In other words, while individual factors significantly influence beliefs in conspiracy theories, as past research demonstrated (e.g., Douglas et al, 2017), their plausilibity should also be examined depending on the context (Alper & Yilmaz, 2023). In societies where institutional trust is low and corruption is high, individuals who perceive institutions as lacking transparency may distrust official statements.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, while individual factors significantly influence beliefs in conspiracy theories, as past research demonstrated (e.g., Douglas et al, 2017), their plausilibity should also be examined depending on the context (Alper & Yilmaz, 2023). In societies where institutional trust is low and corruption is high, individuals who perceive institutions as lacking transparency may distrust official statements.…”
Section: Discussionmentioning
confidence: 99%
“…After all, the public might not be concerned about individuals expressing rational concern about their government but worry more about individuals whose actions are based on perceptions that are scientifically unwarranted and not shared by the broader population (Sutton & Douglas, 2020), such as the idea of governments and scientists being involved in a scheme to convince individuals that the world is round while it is indeed flat or that the US government faked the Apollo moon landing. While it might be possible to distinguish reasonable doubt from scientifically unwarranted theories on a theoretical level (see Alper & Yilmaz, 2023; Brotherton, 2013; Nera & Schöpfer, 2023, for attempts to do so), the question remains on how to operationalize these scientifically unwarranted theories. The fact that belief in such theories is often correlated (e.g., Swami et al, 2017; Wood et al, 2012) has led scientists to use scales consisting of several such scientifically unwarranted theories, as for example in the Belief in Conspiracy Theories Inventory (Swami et al, 2010).…”
Section: Circular Reasoningmentioning
confidence: 99%
“…Although core definitions of conspiracy theories do not inherently refer to their level of verisimilitude, psychological research has primarily focused on the irrational and epistemically problematic aspects of conspiracy theories (Alper & Yilmaz, 2023).…”
Section: Differentiating the Correlates Of Judgments Of Plausible Vs ...mentioning
confidence: 99%